School outbreak of coxsackievirus A16 in Antipolo City, Philippines, October 2022 - Garcia III, Daniel SP; Faiyaz MF, Alireza S; Rebato, Nino D; Blanco-Payuyo, Mariz Zheila; Roca, John Bobbie; Lat, Concepcion G (Western Pacific Surveillance and Response, 2025)
Objective: An investigation team was deployed to determine the cause of an outbreak of a cluster of cases of fever and rash in a public elementary school in Antipolo City, Philippines, after the Public Health Unit was notified on 24 October 2022. The team also aimed to identify the source of the outbreak and to guide prevention measures. Methods: Active case-finding for hand, foot and mouth disease was conducted at the school. A suspected case was defined as any learner who developed acute febrile illness with a papulovesicular rash on the palms and soles of the feet during 16–30 October 2022. Interviews with key informants were conducted and included school staff and parents. Oropharyngeal swabs were collected for polymerase chain reaction (PCR) testing. Results: Nineteen suspected cases of hand, foot and mouth disease were detected, predominantly in grade 1 learners (16, 84%). Most cases (14, 74%) were 6 years old, and just over half were male (11, 58%). The first case occurred in a 6-year-old in grade 1 who attended class with a papulovesicular rash. Twelve learners (63%) from the same section developed symptoms, two of whom were seatmates of the first case. Two out of the 10 swabs collected were tested by PCR, both of which were positive for coxsackievirus A16. Discussion: The causative agent of this outbreak was identified as coxsackievirus A16. Disease transmission occurred through close contact with the index case and possibly through shared classroom objects. Follow-up actions included dissemination of a memorandum about preventing the disease to all public elementary and secondary schools that emphasized symptom screening (i.e. for fever and rash), self-isolation at the onset of symptoms, regular disinfection of classroom surfaces and regular handwashing, especially before and after eating.